2023
DOI: 10.5312/wjo.v14.i2.55
|View full text |Cite
|
Sign up to set email alerts
|

Fungal arthritis: A challenging clinical entity

Abstract: There has been an increasing incidence of fungal infections in recent years. Rarely joints are also affected by fungal infections. Mainly, these infections develop in prosthetic joints, but sometimes native joints are also involved. Candida infections are mostly reported, but patients may also develop infections secondary to non- Candida fungi, especially Aspergillus . Diagnosis and management of these infections is challenging and may involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this study, the pathological examination revealed the presence of fungal mycelium in serial sections of the vertebral lesion tissue, as indicated by positive results of PASM and PAS staining. Consequently, the anti-TB treatment was replaced with a combination of ketoconazole and itraconazole as antifungal therapy, which is widely acknowledged as essential and efficacious for managing fungal osteomyelitis [ 69 ]. In our review, a favorable outcome was observed in 9 out of 40 cases (22.5%) who received prolonged treatment with antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pathological examination revealed the presence of fungal mycelium in serial sections of the vertebral lesion tissue, as indicated by positive results of PASM and PAS staining. Consequently, the anti-TB treatment was replaced with a combination of ketoconazole and itraconazole as antifungal therapy, which is widely acknowledged as essential and efficacious for managing fungal osteomyelitis [ 69 ]. In our review, a favorable outcome was observed in 9 out of 40 cases (22.5%) who received prolonged treatment with antifungal agents.…”
Section: Discussionmentioning
confidence: 99%